A new subspecies record for the flora of Turkey: Artemisia santonicum L. subsp patens (Neilr.) KMPerss. (Asteraceae) - Kursat, Murat; Turkoglu, Ismail; Civelek, Semsettin; Tabur, Selma (Tubitak Scientific & Technological Research Council Turkey, 2011)
[Abstract Not Available]
Keywords: Lamiaceae